Assessment of cardiovascular risk factors in patients with subclinical hypothyroidism. Issue 6 (1st December 2016) - Maleki, Narges; Kazerouni, Faranak; Hedayati, Mehdi; Rahimipour, Ali; Maleki, Hossein
Abstract : Objective Overt hypothyroidism is associated with accelerated arteriosclerosis and cardiovascular disease (CVD). Whether subclinical hypothyroidism (SCH) is also associated with increased cardiovascular risk remains controversial. The present study aimed to evaluate risk factors for CVD in SCH patients in comparison to healthy controls. Methods We assessed common lipid variables, fasting glucose, insulin, malondialdehyde (MDA), total bilirubin (TB) and homeostasis model assessment (HOMA) index in 34 patients with SCH and 34 healthy controls. Results In SCH there was an elevated total cholesterol (TC) ( P < 0.01), low-density lipoprotein cholesterol (LDL-C) ( P < 0.01) and fasting glucose ( P < 0.001) concentration, a diminished TB value ( P < 0.001) and borderline elevated triglycerides (TG) (not reaching the limit of significance, P = 0.063). LDL-C to HDL-C ratio was also elevated ( P < 0.05). MDA and HOMA index were higher in the SCH subjects but this difference was not statistically significant. Insulin, high-density lipoprotein cholesterol (HDL-C) remained unaltered. TSH was positively correlated with TC, LDL-C, fasting glucose ( P < 0.01) and MDA ( P < 0.001) and inversely correlated with TB ( P < 0.01). HOMA index was positively correlated with TG ( P < 0.001) and negatively correlated with HDL-C ( P < 0.01). In the SCH group, MDA was positively correlated with TC, LDL-C and TG ( P < 0.05). TB was negatively correlated with TG ( P < 0.05). Conclusion Our findings suggest that cardiovascular risk might be increased in patients with subclinical hypothyroidism which provides a possible explanation for the early detection and treatment of such individuals.